2011
DOI: 10.1375/twin.14.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Motor Development of Triplets: A Japanese Prospective Cohort Study

Abstract: We analyzed whether motor development in early life is different between singletons and triplets in Japan. The motor development was reported by mothers by postal questionnaire for 1,121 triplet children and in regular health check-ups for 13,906 singleton children. Children who were suspected of having neurological abnormality or disability were excluded from the analysis. The ages of milestone achievements were significantly higher in triplets for each outcome compared to singletons. Further, after adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Many previous studies have found neurological deficits to relate to VLBW, preterm birth, and multiples (21,(33)(34)(35)(36)(37)(38)(39). A metaanalysis indicated that non-right-handedness is more common in those with intellectual disabilities compared with those with no intellectual disability (40).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have found neurological deficits to relate to VLBW, preterm birth, and multiples (21,(33)(34)(35)(36)(37)(38)(39). A metaanalysis indicated that non-right-handedness is more common in those with intellectual disabilities compared with those with no intellectual disability (40).…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence for this in Japanese children, because very low birthweight triplets were ahead of very low birthweight singletons in motor development in early childhood. 7 Further, we used no information on zygosity because it was available only for part of the cohort, and stratification of the results by zygosity would have decreased the statistical power in the analysis stratified by parental SEP and maternal birth cohort. However, in our previous study in which we used self-reported zygosity and some of the same data as in this study, we found no major differences in height, BMI or muscle strength between monozygotic and dizygotic twins.…”
Section: This Results Suggestsmentioning
confidence: 99%
“…Thus, low birthweight and low gestational age is expected to show different associations with the development of singletons when compared with twins and triplets. We found evidence for this in Japanese children, because very low birthweight triplets were ahead of very low birthweight singletons in motor development in early childhood . Further, we used no information on zygosity because it was available only for part of the cohort, and stratification of the results by zygosity would have decreased the statistical power in the analysis stratified by parental SEP and maternal birth cohort.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical growth and development features of twins and triplets in childhood were also extensively analyzed as part of the study (Yokoyama et al, 1995d, 2005, 2008, 2009, 2011a, 2011b, 2012). The present dataset represents the largest triplet sample in the world for which accurate data on age after birth are available.…”
Section: Focus Of the Studymentioning
confidence: 99%